2012
DOI: 10.1002/jclp.21938
|View full text |Cite
|
Sign up to set email alerts
|

The Discrepancy between Subjective and Objective Measures of Sleep in Older Adults Receiving CBT for Comorbid Insomnia

Abstract: This is the first CBT-I outcome study to analyze discrepancy changes and demonstrate that these changes account for a significant portion of self-report outcome. In addition, improved sleep quality as measured by a decrease in percentage of stage N1 sleep following treatment may be one mechanism that explains why sleep estimation is more accurate following CBT-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 34 publications
11
49
1
Order By: Relevance
“…In the total sample, transformations did not normalize distributions for STAI, MMSE, and all SOL and WASO variables. Extreme values in SOL and WASO variables were visually determined to be within the range of natural fluctuations relative to previous studies in older adults (Lund et al 2012; Kay et al, 2013). Where appropriate, non-parametric tests were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the total sample, transformations did not normalize distributions for STAI, MMSE, and all SOL and WASO variables. Extreme values in SOL and WASO variables were visually determined to be within the range of natural fluctuations relative to previous studies in older adults (Lund et al 2012; Kay et al, 2013). Where appropriate, non-parametric tests were used.…”
Section: Methodsmentioning
confidence: 99%
“…One study in a small sample of older adults with insomnia reported that behavioral interventions improved both actigraphy and sleep diary WASO but these changes (subjective and objective) did not correlate within individuals (e.g., Brooks et al 1993). A more recent study in older adults with insomnia (OAI) showed CBTI significantly decreased negative sleep discrepancy (PSG vs. sleep diary) in SOL but not WASO or TST (Lund et al 2012). More importantly, pre- to post-treatment changes in sleep discrepancy mediated the association between stage N1 sleep changes and sleep efficiency (SE=percent of time in bed spent sleeping) improvements (Lund et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, insomnia symptoms were collected mainly via subjective reports. Future studies may supplement subjective reports with objective measures, including actigraphy and polysomnography [10]. Currently, there is not sufficient empirical support for the causal direction of the relationships among sleep, mood, and IL-6 [2,3].…”
Section: Figmentioning
confidence: 99%
“…2 Health promotion strategies in an addiction recovery model should address quality-of-life enhancements for individuals and their families including optimizing sleep through sustained recovery. Examples of such strategies include cognitive-behavioral therapy for insomnia (CBT-I), which targets behaviors, cognitions, and associations that negatively affect sleep, 3 and is the most common and well-accepted nonpharmacologic treatment of insomnia. CBT-I has been tested on alcohol-dependent populations and has demonstrated improvements in general sleep quality, 4 sleep efficiency, 59 wake after sleep onset (WASO), 7,8 and general fatigue.…”
mentioning
confidence: 99%